Network and Information Systems (NIS) Regulations - A pocket guide for digital service providers - Calder, Alan (ITGP, 2018)
This pocket guide is a primer for any DSPs (digital service providers) that needs to comply with the NIS Regulations, and explores who they are, and why the NIS Regulations are different for them.